PENGARUH MANAJEMEN PERUBAHAN, GAYA KEPEMIMPINAN DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DI DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA PADANG PANJANG - Zulfa Hidayah; Nofrivul; Rizal (STKIP Subang, 2024)
The main problem in this study is the change management carried out and the application of different leadership styles and workloads. The purpose of this study was to determine the effect of change management, leadership style and workload on employee performance at the Padang Panjang City Library and Archives Office. The type of research used is field research with a quantitative approach. Data collection techniques through questionnaires and documentation. The data analysis technique in this study used the classical assumption test, multiple linear regression test, partial test (t-test) and simultaneous test (F-test) with the help of SPSS 26.0 for windows. The results showed that partially change management affects employee performance at the Padang Panjang City Library and Archives Office. Leadership style affects employee performance at the Library and Archives Office of Padang Panjang City. Workload affects employee performance at the Library and Archives Office of Padang Panjang City. Then in simultaneous testing it was found that together change management, leadership style and workload affect employee performance at the Padang Panjang City Library and Archives Office.